Numeracy skill development in prospective mathematics teachers: Challenges and opportunities in real-world contexts - Winarni, Sri; Kamid; Marzal, Jefri; Asrial (Journal on Mathematics Education, 2025)
Numeracy skills are essential for prospective mathematics teachers as they bridge mathematical concepts with real-life applications. However, many prospective mathematics teachers face challenges in applying these concepts to practical situations. This study aims to analyze the conceptual and procedural errors made by prospective mathematics teachers when solving numeracy problems within the context of "Save Our Water." A descriptive research design was employed, utilizing a numeracy test adapted from the Minimum Competency Assessment (MCA) and semi-structured interviews as research instruments. The study involved 30 prospective mathematics teachers from the University of Jambi, Indonesia. The findings revealed that conceptual errors primarily stemmed from reliance on rote memorization of formulas without a deeper conceptual understanding. Procedural errors were attributed to difficulties in unit conversion, incorrect formula application, and improper manipulation of formulas. To address these issues, the study recommends incorporating contextual approaches, problem-based learning, and project-based learning strategies that connect mathematical concepts to real-world contexts. Additionally, the use of visual aids, such as diagrams and 3D models, is suggested to enhance conceptual understanding and strengthen the connection between abstract concepts and practical applications. Future research should investigate the effectiveness of these instructional approaches in improving numeracy skills and enhancing the teaching readiness of prospective mathematics teachers.